THE LANGUAGE ATTITUDE OF CULINARY ENTREPRENEURS IN BANJARMASIN - Siti Jamzaroh (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2019)
This study aims to describe the language attitude of culinary business entrepreneurs, and the culinary business language behavior.in Banjarmasin Type of research sociolinguistic research The method used in collecting data was by using questionnaire, data processing by calculation with Likert scale, the data is analyzed and presented in the form of diagrams and tables. The results found are a) the attitude of the language towards Indonesian language associated with norm awareness, loyalty, and cognition of culinary entrepreneurs in Banjarmasin is generally low (C); this is caused by the assumption that language is not important, and what is preferred is the market or market; b) the response of culinary entrepreneurs to the linguistic phenomenon in the world of chemistry shows a trend that is better than language attitudes. This mean s that they can adequately judge whether the use of the language used in the business of graft is wrong or right, good or bad.